Mortgage Supply and Housing Rents - Gete, Pedro; Reher, Michael (Review of Financial Studies, 2018)
We show that a contraction of mortgage supply after the Great Recession has increased housing rents. Our empirical strategy exploits heterogeneity in MSAs' exposure to regulatory shocks experienced by lenders over the 2010-2014 period. Tighter lending standards have increased demand for rental housing and have led to higher rents, depressed homeownership rates and an increase in rental supply. Absent the credit supply contraction, annual rent growth would have been 2.1 percentage points lower over 2010-2014 in MSAs where lending standards rose from their 2008 levels.